Investigating the Students’ Challenges and Opportunities in Self-Directed English Language Learning Through Social Media Content: A Case Study of Merdeka Curriculum School - Fahrezi Munthe, MHD. Husri Zaini; Dewi, Utami (Universitas PGRI Sumatera Barat, 2024)
This study examines the challenges and opportunities encountered by students in self-directed English language learning through social media content within the framework of Merdeka Curriculum schools. Semi-structured interviews were conducted with five junior high school students using a qualitative approach. The thematic content analysis reveals several key challenges, such as difficulties selecting appropriate content, distractions from non-academic material, and a lack of guidance. However, students also identified important opportunities, such as flexible learning times and places, increased motivation, access to various resources, and opportunities to interact with native speakers and peers from different backgrounds. The results of this study highlight the importance of more structured strategies and guidelines to help students effectively utilize social media in English language learning.